Causation as a factor and goal in typological comparisons - LaPolla, Randy J. (2018)
For some time in the field of typology there has been debate about the nature of the categories or concepts used in typological comparison and the difference between these categories or concepts and descriptive categories (the categories used in describing individual languages). In early 2016 an extensive debate on this topic on Lingtyp, the listserv list for the Association for Linguistic Typology, 1 resulted in an exchange in Linguistic Typology 20(2) on this topic, with position papers written by some of the participants in the online debate, in response to a series of questions from the Editor of Linguistic Typology. There was no clear resolution to the differences between the two main camps involved in the debate, but a follow-up to that debate earlier this year (2017) led to pinpointing the key issue that divides the two camps, causality, and I’d like to present it here as an important issue we should be aware of.